Functional beverages: recent trends and prospects as potential meal replacers - Ravneet Kaur; Shubhra Shekhar; Kamlesh Prasad (Food Materials Research)
Increased consciousness for health, well-being, and changes in eating habits, such as a shift towards veganism among the masses, has resulted in rapid growth in the functional foods market. Functional beverages are one of the core areas of research and development among various functional foods. However, ready to drink beverages have some limitations in terms of shelf life, storage, and transportation, so the future trends in the beverage industry could be more towards powdered beverages and ready-to-reconstitute instant mixtures. Due to a sedentary lifestyle, people are trying to follow a balanced diet for weight management, and weight loss programs are also gaining importance. One such category that has come into focus is meal replacements. Nutritionally balanced beverage mixtures have the potential to be used as meal replacements. This review is based mainly on recent and ongoing trends in beverages, such as functional beverages based on dairy sources, fruits and vegetables, cereals-legumes, and millets-based beverages. It also focuses on the future aspects in the beverage industry with a brief about instant beverage powders. Beverages as potential meal replacement products are the major future aspect in this area. This review also discusses the optimization techniques used for the development of beverage mixes.